Probiotics Exhibit Strain-Specific Protective Effects in T84 Cells Challenged With Clostridioides difficile-Infected Fecal Water - Gaisawat, Mohd Baasir; Lopez-Escalera, Silvia; MacPherson, Chad W.; Iskandar, Michèle M.; Tompkins, Thomas A.; Kubow, Stan (Frontiers in Microbiology, 2022)
Clostridioides (C.) difficile infection (CDI) is frequently associated with intestinal injury and mucosal barrier dysfunction leading to an inflammatory response involving neutrophil localization and upregulation of pro-inflammatory cytokines. The severity of clinical manifestations is associated with the extent of the immune response, which requires mitigation for better clinical management. Probiotics could play a protective role in this disorder due to their immunomodulatory ability in gastrointestinal disorders. We assessed five single-strain and three multi-strain probiotics for their ability to modulate CDI fecal water (FW)-induced effects on T84 cells. The CDI-FW significantly (p < 0.05) decreased T84 cell viability. The CDI-FW exposed cells also exhibited increased pro-inflammatory cytokine production as characterized by interleukin (IL)-8, C-X-C motif chemokine 5, macrophage inhibitory factor, IL-32 and tumor necrosis factor ligand superfamily member 8. Probiotics were associated with strain-specific attenuation of the CDI-FW mediated effects whereby S. boulardii CNCM I-1079 and L. rhamnosus R0011 were most effective in reducing pro-inflammatory cytokine production and in increasing T84 cell viability. ProtecFlorTM, L. helveticus R0052 and B. longum R0175 showed moderate effectiveness, and L. rhamnosus GG R0343 along with the two other multi-strain combinations were the least effective. Overall, the findings showed that probiotic strains possess the capability to modulate the CDI-mediated inflammatory response in the gut lumen.